Liquid-liquid equilibria data for the separation of ethylbenzene/styrene mixtures using ammonium-based deep eutectic solvents - Mulyono, Sarwono; Hizaddin, Hanee Farzana; Wazeer, Irfan; Alqusair, Omar; Ali, Emad; Hashim, Mohd Ali; Hadj-Kali, Mohamed K. (Elsevier, 2019)
Separation of styrene from ethylbenzene is challenging because of their close boiling points and similar chemical characteristics. In this study, we utilized three ammonium-based deep eutectic solvents (DESs) with glycols as hydrogen bond donors to separate styrene from ethylbenzene via liquid-liquid extraction at room temperature and atmospheric pressure, with styrene concentration in the feed mixture ranging from (10 to 80) wt%. Consistency of the experimental data was ascertained by Othmer-Tobias and Hand correlations, and the NRTL binary interaction parameters were also validated for thermodynamic consistency. Distribution ratios of styrene were found to be comparable to that obtained using ionic liquids, although the selectivity values were much lower. The ternary liquid-liquid equilibria for the systems {ethylbenzene (1) + styrene (2) + DES (3)} were correlated with the NRTL model and predicted using the COSMO-RS approach. The average RMSD from the experimental data for NRTL correlation is 1.41% and for COSMO-RS prediction is 4.74%. © 2019 Elsevier Ltd